2023
DOI: 10.1108/jhti-10-2022-0488
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital before and during COVID-19 in the hotel industry: the moderating role of tangible assets

Abstract: PurposeThe study aims to assess the relative impact of intellectual capital (IC) as opposed to tangible assets on profitability and employee performance in hotels in Serbia before and during the coronavirus disease 2019 (COVID-19) pandemic.Design/methodology/approachThe current study was undertaken in 2019, the year before COVID-19, and 2020, the year of COVID-19's major impact. This study utilizes the Value-Added Intellectual Coefficient (VAIC) as a measure of efficient use of IC. Financial data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 88 publications
(167 reference statements)
1
9
0
Order By: Relevance
“…Although, traditionally, research has associated tourism activities to a low level of staff training and a limited presence of graduates (Hjalager, 2002), the importance of staff training for tourism firm competitiveness has been increasingly acknowledged in studies carried out in recent decades (Ognjanovic et al, 2023;Yam et al, 2004). Staff training could affect the absorptive capacity of tourism organisations (Thomas and Wood, 2015), increase the efficiency of managing intellectual capital (Ognjanovic et al, 2023) and influence innovation (Ottenbacher and Gnoth, 2005). Furthermore, empirical analyses have observed that trained employees improve innovation and profits (Marco-Lajara et al, 2018).…”
Section: H4mentioning
confidence: 99%
“…Although, traditionally, research has associated tourism activities to a low level of staff training and a limited presence of graduates (Hjalager, 2002), the importance of staff training for tourism firm competitiveness has been increasingly acknowledged in studies carried out in recent decades (Ognjanovic et al, 2023;Yam et al, 2004). Staff training could affect the absorptive capacity of tourism organisations (Thomas and Wood, 2015), increase the efficiency of managing intellectual capital (Ognjanovic et al, 2023) and influence innovation (Ottenbacher and Gnoth, 2005). Furthermore, empirical analyses have observed that trained employees improve innovation and profits (Marco-Lajara et al, 2018).…”
Section: H4mentioning
confidence: 99%
“…Challenges brought forth by the pandemic aggravated the need of promoting ICIA (Mubarik et al. , 2022; Ognjanovic et al. , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through ICIA organizations leverage their value even in testing times like the COVID-19 pandemic. Challenges brought forth by the pandemic aggravated the need of promoting ICIA (Mubarik et al, 2022;Ognjanovic et al, 2023).…”
Section: Teacher As a Servant Leader (Tasl) And Intellectual Capital-...mentioning
confidence: 99%
See 2 more Smart Citations